DOKTRIN PERSEMBAHAN PERSEPULUHAN DALAM PERJANJIAN LAMADAN RELEVANSINYA DENGAN GEREJA MASA KINI - Mahir Zagoto; Hery Budi Yoshep (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
If observed deeply and seriously about the world of science, there will be shifts, especially in interpreting something. And changes in interpreting something that is no longer in accordance with the meaning previously held will cause chaos and will lead to a split. This situation often occurs in the body of the church and it is triggered because interpreting a word or sentence is no longer based on the actual basis but in the interpretation maybe because of envy of someone or maybe because it fulfills the personal taste of an interpreter. One example is the establishment of the Protestant church. This was motivated by the publication of the Indulgence letter in the Middle Ages offered by the Catholic Church. Indulgence is a letter of temporary punishment or torment for sin because sins are forgiven. Problems in the church have always existed, recently many have opposed the tithing offering. With a loud voice conveying the inspiration to reject the tithing offering in the church. There are churches that argue that the tithing offering is no longer in its time because the tithing offering existed in the time of the Torah. One example of opposing tithing is Budi Asali. He said, "I do not doubt that there are many pastors who do make the church a business, emphasizing tithing with a jerk motivation to enrich themselves. That clearly has no place at all. Congregations who do not give tithing for their own wealth are much greater robbers of God. It is truly unfortunate if there are servants of God who oppose the Word of God. This kind of attitude is one of the attitudes that indirectly teaches the congregation to oppose the Word of God or cancel the Word of God related to tithing that has been carried out since Abram.